The SmartAG partner: CCAFS East Africa Quarterly Newsletter, January - March 2018 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
We are pleased to share with you our SmartAg Partner newsletter, highlighting policy engagement and ongoing research from the first quarter of 2018. In February, the CCAFS East Africa team convened in Arusha, Tanzania, for a strategy meeting that brought together 65 stakeholders comprising of researchers, regional policymakers, experts from governments, private sector, multilateral international organizations and NGOs from East Africa and around the world to develop an integrated research for development strategy for CCAFS East Africa. The CCAFS strategy meeting was held back to back with the kick-off meeting of the Food & Business GCP4 projects which took place on 6–7 February. The eight research projects funded in the fourth Global Challenges Programme call will be implemented in East Africa beginning 2018 and focus on how to scale climate-smart agriculture practices, private sector engagement and inclusive business model development in East Africa. The new projects will contribute to the achievement of the regional strategy for development. To enhance climate change and agriculture policy processes with key research and development actors from Africa, we established the Climate and Agriculture Network for Africa (CANA), a knowledge sharing web-based platform in 2014. Since then, we have continued to host webinars and online discussions via the platform. From 23 April to 21 May 2018, we shall host an online discussion on Partnerships, innovations and financing for youth in climate-smart agriculture. Kindly join us in the discussion as we dialogue on how to engage African youth in climate-smart agriculture.